Construction and evaluation of China older-adult care service smart supply chain system - Dai, You-Yu; Liu, Guanlong; Sun, Long (Frontiers in Public Health, 2023)
Introduction As the aging of the population continues to deepen, the pressure on social pensions is gradually increasing, and the issue of assistance has become a problem that must be solved. With the development of science and technology, people’s living standard is constantly improving. The older-adult care services expected by the older-adult are wider than meeting the basic daily needs of individuals. The current industry should also consider combining modern science and technology with the older-adult care service industry to serve older-adult better and enable older-adult care service providers to move towards the service needs that make people happier and healthier. This research is about constructing and evaluating China’s older-adult care services smart supply chain. Methods Based on the research results of previous scholars, this paper divides the Sun construction of the smart supply chain of China endowment service into four aspects: policy aspect, economic aspect, social aspect, and technical aspect; the four significant elements are divided into the first-level indicators, and 16 second-level indicators are divided under the first-level indicators. The importance and satisfaction of each evaluation index were obtained by distributing questionnaires to the managers who study the supply chain and the employees who are related to the old-age service. Results and discussion After the reliability analysis, the importance-performance analysis (IPA) quadrant analysis chart of the evaluation index was constructed using importance-performance analysis. The index of creating a smart supply chain system for China’s old-age service is given priority, the supply chain system of China’s old-age care service is further improved, and the social security of China’s old-age service is enlarged.